Model Sosial Budaya bagi Penyelenggaraan Transmigrasi di Irian Jaya - Parsudi Suparlan (Antropologi Indonesia, 1998)
In this article, the author brings forth the need for a cultural perspective in examining and handling the problem of transmigration. He concentrates on transmigrants and their settlements, and emphasizes the importance of transmigration settlement planning that accord with the culture of the future transmigrant, along with settlement planning that takes into account its future as a center of social and economic growth and social integration in the area. Drawing from his experience with transmigration in Irian Jaya, the author shows how the transmigrants of the village of Jambal and most of the local ethnic groups show varying, sometimes opposing, characteristics. He points out that transmigrants from Java are oriented toward their urban centers, but are then placed at relatively isolated areas. Thus it should come as no surprise if these transmigrants tend to abandon their new settlement for the city. The author suggests that the transmigration program can be said to be successful if it can be shown that the settlers are in fact faring better in their new area. Here, transmigration settlements cannot be regarded as mere settlement, but as arenas for the improvement of their habitants' prosperity. They must be viewed as part of the region's development and administrative system. The author completes the article with a model of transmigration for Irian Jaya that rests on a pluralistic model of society rather than a model of assimilation.